(untitled) (SCIENCE TIME JOURNAL, 2023)
This article explores the use of innovative technologies in teaching foreign languages. It highlights various ways in which technology can enhance language learning, including blended learning approaches, data-driven insights, adaptive feedback and assessment, authentic and multimedia content, remote learning and virtual classrooms, artificial intelligence in language tutoring, cultural immersion through virtual reality, and accessibility and inclusivity. The article emphasizes the potential of these technologies to provide personalized and engaging language learning experiences. It also emphasizes the importance of educators staying informed and adapting their teaching practices to leverage the benefits of innovative technologies.